Pengaruh Karakter Mahasiswa dan Manajemen Waktu Terhadap Perilaku Disiplin pada Kampus Sekolah Tinggi Ilmu Ekonomi Pancasetia Banjarmasin - A. Razib; Anthonius J. Karsudjono; Fredy Jayen (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
On the STIE Pancasetia Banjarmasin campus, the purpose of this study is to ascertain how student character and time management influence disciplinary behavior. Quantitative research covers this particular area of study. Procedure for studying with the assistance of a Google Structure 674 S1 management and accounting students from the Stie Pancasetia Campus in Banjarmasin took part in this study in 2022. On the STIE Pancasetia Banjarmasin campus, the study found that the variables of student character and time management had a positive and significant effect simultaneously on disciplinary behavior. On the STIE Pancasetia Banjarmasin campus, variables related to student character and time management have a positive and significant impact on disciplinary behavior. Because it has the highest beta coefficient value among the variables related to student character, the time management variable has the greatest impact on this study